Effects of dissolved organic phase composition and salinity on the engineered sulfate application in a flow-through system - Saeid Shafieiyoun (14151654) (2020)
Engineered sulfate application has been proposed as an effective remedy to enhance the rate-limited biodegradation of petroleum-hydrocarbon-contaminated subsurface environments, but the effects of dissolved organic phase composition and salinity on the efficiency of this method are unknown. A series of flow-through experiments were conducted for 150 days and dissolved benzene, toluene, naphthalene, and 1-methylnaphthalene were injected under sulfate-reducing and three different salinity conditions for 80 pore volumes. Then, polycyclic aromatic hydrocarbons (PAHs) were omitted from the influent solution and just dissolved benzene and toluene were injected to investigate the influence of dissolved phase composition on treatment efficiency. A stronger sorption capacity for PAHs was observed and the retardation of the injected organic compounds followed the order of benzene < toluene < naphthalene < 1-methylnaphthalene. Mass balance analyses indicated that 50 and 15% of toluene and 1-methlynaphtalene were degraded, respectively. Around 5% of the injected naphthalene degraded after injecting > 60 PVs influent solution, and benzene slightly degraded following the removal of PAH compounds. The results showed substrate interactions and composition can result in rate-limited and insufficient biodegradation. Similar reducing conditions and organic utilization were observed for different salinity conditions in the presence of the multi-component dissolved organic phase. This was attributed to the dominant microbial community involved in toluene degradation that exerted catabolic repression on the simultaneous utilization of other organic compounds and were not susceptible to changes in salinity. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-020-07696-6